Kemampuan Komunikasi Matematis dan Kemandirian Belajar Siswa Melalui Flipped Classroom-Collaborative Learning - Detiana Amir; Rahmah Johar; Mailizar Mailizar (Universitas Syiah Kuala, 2020)
This study aimed to describe students' mathematical communication skills, examine their improvement and describe students' learning independence during the learning. This study applied a mixed-method approach with a concurrent embedded strategy. Samples were selected by random sampling, 32 Year 10 students from one of the senior high schools in Banda Aceh, Indonesia. The instrument used to obtain data on students' mathematical communication skills during the learning were a daily test, observations, and interviews. The instrument used to obtain data on the improvement of students 'mathematical communication skills after learning were pretest and posttest. While the instrument used to describe students' learning independence during the learning was a questionnaire. Data analysis was conducted using a rubric to assess mathematical communication skills, a Paired-sample t-test, and descriptive statistics. The results showed that students could communicate mathematically orally and in writing related to the trigonometric function graph material during the learning. Furthermore, there was an increase and a significant effect on students' mathematical communication skills scores. This study also showed that students have independent learning during the learning using Flipped Classroom-Collaborative Learning (FC-CL). Therefore, teachers are expected to expand the application FC-CL to other materials.